Influence of Fermented Cocopeat on Seedling Vigour in some Vegetables, Marigold and Pigeon Pea - S C Kotur (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Seedlings of four solanaceous, two cruciferous, five cucurbitaceous vegetables, and, marigold and pigeon pea were grown in pro-trays filled with 'Arka Fermented' coco-peat or on conventional raised bed. Seedlings grown on raised bed were superior in all the crops excepting capsicum. Pigeon pea recorded significantly longer tap root in pro-trays with the root getting matted at the base of the coco-peat plug. The plug is rendered redundant at transplanting. To enhance the vigour of 'Arka Ananya' tomato seedlings in pro-trays, modification in growth medium was attempted by blending soil in various proportions and adding 0.2% humic acid to the irrigation water. Blending cocopeat:soil at 3:1 ratio caused some improvement compared to that with cocopeat alone or 1:1 and 1:3 blends of cocopeat:soil. Soil alone, placed in the pro-tray, also failed to equal the high seedling vigour produced by conventional raised bed method. Addition of 0.2% humic acid in water used for irrigating pro-trays showed no improvement in seedling vigour. Reduced vigour of seedlings raised in pro-trays in several vegetables, and poor performance of such seedlings in tomato, cabbage and cauliflower crops in the field, indicates a need for further improvement in the technology.